Podwójna przyjemność – spotkanie z Krystyną i Stefanem Chwinami - Zatorska, Matylda (Tematy i Konteksty, 2016)
On May 24th, 2014 the University of Rzeszów hosted the conference “Stefan Chwin – Spaces of Imagination” whose honoured guests were Stefan Chwin, novelist and literary historian, and Krystyna Chwin, poet and publisher. The first part of the conference was the lecture by Professor Chwin, entitled “Great Central European deportations of the 20th century from the axiological perspective. Challenges for Literature”, whereas the second part included the meeting with the literary couple. The event was organized by the Literary Studies Section of the Academic Association of Scholars of Polish Studies and by the editorial board of the literary and artistic quarterly “Fraza”.